2020
DOI: 10.1002/ange.201914421
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of 1,5‐Oxygen⋅⋅⋅Chalcogen Interactions in Enantioselective Isochalcogenourea Catalysis

Abstract: The importance of 1,5‐O⋅⋅⋅chalcogen (Ch) interactions in isochalcogenourea catalysis (Ch=O, S, Se) is investigated. Conformational analyses of N‐acyl isochalcogenouronium species and comparison with kinetic data demonstrate the significance of 1,5‐O⋅⋅⋅Ch interactions in enantioselective catalysis. Importantly, the selenium analogue demonstrates enhanced rate and selectivity profiles across a range of reaction processes including nitronate conjugate addition and formal [4+2] cycloadditions. A gram‐scale synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 68 publications
0
14
0
1
Order By: Relevance
“…[29] Extensive structural investigations,b oth in solution using nuclear Overhauser effect spectroscopy and in the crystal using X-ray structural analyses,w ere able to demonstrate the importance of these oxygen-sulfur interactions for this catalysis. [30] Kinetic studies showed asignificantly higher catalytic activity for the analogous isoselenourea derivatives.C omputational studies,s uch as the first theoretical investigation on chalcogen-chalcogen interactions in 2006, [7,8] demonstrated the electron delocalization as n Ch !s* Ch-C interactions.…”
Section: Viewpointmentioning
confidence: 97%
“…[29] Extensive structural investigations,b oth in solution using nuclear Overhauser effect spectroscopy and in the crystal using X-ray structural analyses,w ere able to demonstrate the importance of these oxygen-sulfur interactions for this catalysis. [30] Kinetic studies showed asignificantly higher catalytic activity for the analogous isoselenourea derivatives.C omputational studies,s uch as the first theoretical investigation on chalcogen-chalcogen interactions in 2006, [7,8] demonstrated the electron delocalization as n Ch !s* Ch-C interactions.…”
Section: Viewpointmentioning
confidence: 97%
“…61 Chalcogen bonding interactions have been implicated in the mechanism of isochalcogenureacatalyzed kinetic resolutions of secondary benzylic alcohols. 62 These reactions proceed via an acylated intermediate containing a carbonyl-chalcogen contact (Figure 10C). Indeed, the molecular orbitals and NBOs of these intermediates bear a striking resemblance to those observed in molecular balances (Figure 10C cf.…”
Section: Metallophilic Interactionsmentioning
confidence: 99%
“… 19 When the central polarizable E atom belongs to Group VI of the periodic table, the term chalcogen bonding (EB, known also as ChB) is used to describe the interaction between a positively polarized chalcogen atom and a Lewis base. 20 22 Despite recent developments in catalysis 23 28 and sensing, 25 , 30 EB interactions have been mainly exploited in crystal engineering, 31 , 32 providing a distinctive series of persistent recognition motifs. 33 36 The structure of the most part of these chalcogen-bonding synthons builds on a heterocyclic scaffold, in which the chalcogen bond donors and acceptors are proximal to each other, 37 39 thus effectively developing macrocyclic 40 42 and wire-like 43 , 44 supramolecular architectures.…”
Section: Introductionmentioning
confidence: 99%